PENGARUH KONSENTRASI EKSTRAK BAWANG MERAH DAN LAMA PERENDAMAN STEK JAMBU AIR MADU VARIETAS DELI HIJAU (Syzygium aqueum L.) - Jinjing Ario Silitonga; T. Edy Sabli; Fathurrahman, F. (DINAMIKA PERTANIAN, 2019)
This study was conducted to determine the effects of interaction and the main response of the onion extract concentration and soaking time on cuttings guava water honey of green Deli variety (Syzygium aqueum L.). A completely randomized design (CRD) factorial was used in this study, consisting of 2 factors. The first factor was the concentration of onion extract consisting of 4 levels, i.e control, 100 g, 300 g, and 500 g of onion extract per 100 ml water. The second factor was the soaking time which consisted of 4 levels, i.e the soaking time of cuttings 3 hours, 6 hours, 9 hours, and 12 hours. The parameters observed were percentage of cuttings grown, age of germination days after planting, number of shoots, number of roots, longest root length, root volume. Observational data were analyzed statistically and continued with Tukey's HSD tests (p< 0.05). The results showed the interaction of onion extract concentration and soaking time had significant effects on the parameters for the percentage of cuttings grown, sprout age, number of shoots, number of roots, longest root length, and root volume. The best treatment was the combination of onion extract 300 g per 100 ml of water and soaking time on 9 hours.